Legal Certainty of Specific Time Work Agreements (PKWTT) Against Outsourced Labor Based Outsourcing Law Number 6 of 2023 concerning Determination Government Regulation in Lieu of Law Number 2 of 2022 Concerning Job Creation Becoming Law - Mellan Noviani; Jum Anggriani (Inovasi Pratama Internasional. Ltd, 2024)
Outsourcing is the use of labor from a third party for certain parts of work in a company. In terms of Human Resources or worker management, the Government continues to make improvements through regulations with the aim of maintaining the stability of relations between business actors and workers. One of them is Job Creation Law Number 11 of 2020 which regulates outsourcing with no limitations on the scope of work that can be outsourced. This changes some of the provisions of Law Number 13 of 2003 concerning employment. Perppu Number 2 of 2022 in conjunction with Law Number 6 of 2023 concerning Ratification of Perppu Number 2 of 2022 concerning Job Creation, where the cluster that regulates employment is newly regulated in this Law, including regarding outsourcing and/or outsourcing with revoke the provisions of the Job Creation Law Number 11 of 2020. In Law Number 6 of 2023 concerning Ratification of Perppu Number 2 of 2022 concerning Job Creation, it is emphasized that outsourcing is regulated more specifically through Government Regulation (PP) Number 35 of 2021 concerning Specific Time Work Agreements, Outsourcing, Working Time and Time Rest, and Termination of Employment. So this creates legal loopholes and uncertainty as per the constitutional rights of citizens regarding welfare rights and as in Article 28 paragraph 1 and paragraph 2. Every person has the right to work and receive fair and decent compensation and treatment in the employment relationship.